Homelessness in the Suburbs: Engulfment in the Grotto of Poverty - Isolde Daiski (Studies in Social Justice, 2012)
This paper describes findings of a research inquiry into the lived experience of homelessness in Peel, a suburban region located in the Greater Toronto Area in Ontario, Canada. It is based on the data from a collaborative project undertaken by members of the Faculties of Health and Education of York University with two local community organizations. The dominant theme of the narratives was that suburban homelessness is similar to being engulfed in a grotto of poverty, isolated from the rest of the community and invisible to it. Once entrapped in the grotto, it is almost impossible to escape from it. There were four sub-themes: (a) falling into the grotto, (b) living/struggling in the grotto, (c) envisioning escape routes from the grotto, and (d) beauty, community and hope in the grotto. Following a discussion of the findings, researchers describe strategies to address homelessness through promotion of social justice for all.